2020
DOI: 10.1101/2020.07.28.224832
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MSK-mediated phosphorylation of Histone 3 Ser28 couples MAPK signaling with early gene induction and cardiac hypertrophy

Abstract: Heart failure is a leading cause of death, developing subsequent to deleterious hypertrophic cardiac remodelling associated with pathologies including hypertension and myocardial infarction. MAPK signalling pathways, acting via transcription factors, play a key role in coordinating the induction of gene expression during hypertrophy. Induction of the immediate early gene (IEG) response, characterised by increased expression of AP-1 factors, is a necessary and early event in this process. How MAPK signalling an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…ET-1 is an endothelium-derived pluripotent factor that is fundamental in developing pathological hypertrophic remodeling (112). In line with this, Emma L. Robinson et al found that the mitogen and stress-activated protein kinase/Brg1/immediate early gene (MSK/Brg1/IEG) axis mediated ET-1 initiated cardiac hypertrophy (113). In addition, Brg1 and Brm could be the upstream factors of ET-1, promoting its expression in a timedependent manner (112).…”
Section: Role Of Sfⅱ Helicases In Cardiac Remodeling and Hfmentioning
confidence: 92%
“…ET-1 is an endothelium-derived pluripotent factor that is fundamental in developing pathological hypertrophic remodeling (112). In line with this, Emma L. Robinson et al found that the mitogen and stress-activated protein kinase/Brg1/immediate early gene (MSK/Brg1/IEG) axis mediated ET-1 initiated cardiac hypertrophy (113). In addition, Brg1 and Brm could be the upstream factors of ET-1, promoting its expression in a timedependent manner (112).…”
Section: Role Of Sfⅱ Helicases In Cardiac Remodeling and Hfmentioning
confidence: 92%
“…Further in vitro and mouse studies revealed that ligands of GPCRs that couple to Gs or Gq (but not Gi), such as angiotensin II, endothelin I, phenylephrine, and isoproterenol, induce pERK T188 , and that this phosphorylation site does not alter ERK activity but instead triggers the nuclear translocation of ERK. Subsequently, pERK T188 has been shown to trigger the activation of nuclear ERK targets such as Elk1, MSK, and c-myc, targets that not only promote cancer but are known to induce cardiomyocyte hypertrophy [ 60 , 61 , 62 ]. Indeed, pERK T188 is increased in human heart failure and hypertrophic mouse hearts [ 26 , 27 , 55 , 56 ].…”
Section: Erk1/2mentioning
confidence: 99%